Automated Modular Application Development = Zautomatyzowane modułowe tworzenie aplikacji - Wołoszyn, Kamil; Piotrowski, Krzysztof (Zielona Góra: Uniwersytet Zielonogórski, Instytut Metrologii, Elektroniki i Informatyki)
This article presents the concepts of Automated Modular Application Development (AMAD), which utilizes automated mechanisms to facilitate and accelerate the software development process. Building on the Sens4U concept and leveraging the tinyDSM middleware, AMAD automates the selection of appropriate sensors and system configurations, minimizing manual user intervention.
Keywords: komputeryzacja; przyrządy pomiarowe; informatyka; technologie informacyjne